The Effects of Urban Transformation Applications on a Place’s Memory: An Analysis on Zagnos Valley in Trabzon - Aslanöz, Ömer; Baş, Güray Yusuf; Heyik, Muhammet Ali (ICONARCH International Congress of Architecture and Planning, 2017)
Cities desire to keep alive their history, life experiences, cultures, customs and transfer to the next generations. In this context, the built environment, which constitutes the main structure of the city, enters the region and constitutes the largest part of the city’s memory. However, with the development of different needs and functions over time, the built environment undergoes some changes parallel to its life cycle. Along with these changes, many cities are unable to maintain their connection with their history. Some of the cities that protect and maintain the memory of the city with strong representations until today are facing the threat of urban transformation. Especially, the destruction under the name of this transformation, which is experienced in the historical regions of the cities, breaks the connections of the city and the history of the city and destroys their life experiences. With the transformation projects realized in the historical cities, the memory of the city is being destroyed and the cities are rapidly involved in the process of identity loss with similar projects. The Place is far from being integrated with individualization, not allowing them to live their identity, their self respect; but transformed into similar units. Whereas a place is the whole of differences which is undeniably the greatest wealth. In accelerated urban transformation applications, especially in today’s Turkey, must be approached with great sensitivity to place’s memory. Otherwise, fast, unplanned and misapplicable practices can create irreplaceable gaps in the place’s memory and this brings many problems like socio-cultural alienation. It is undoubtedly necessary to stand in a long and detailed manner on the practices, effects of urban transformation. In this context, through the urban transformation example in Zagnos valley, which has a strong historical background in the city of Trabzon, the effects of transformation projects on urban memory and urban identity were assessed and aimed at bringing solutions to the problem of memory depletion which comes together with urban transformation projects.